(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The paper is aimed towards investigating the effect of credit risk and debt coverage on profitability of Indian banks. Factors that affect credit risk and debt coverage have been identified through extent literature. The t-test and regression were used to examine the difference between different sectors of Indian commercial banks and to study the effect of credit risk and debt coverage on banks’ profitability. The results implied that there’s significant difference among select public and private banks. Also, regression analysis indicated that the credit risk and debt coverage indicators was statistically significant to predict the profitability ratios.